2020
DOI: 10.5194/essd-12-2607-2020
|View full text |Cite
|
Sign up to set email alerts
|

The Global Space-based Stratospheric Aerosol Climatology (version 2.0): 1979–2018

Abstract: Abstract. A robust stratospheric aerosol climate data record enables the depiction of the radiative forcing of this highly variable component of climate. In addition to the radiative forcing, stratospheric aerosol also plays a key role in the chemical processes leading to ozone depletion. Therefore, stratospheric aerosol is one of the crucial parameters in understanding climate change in the past and potential changes in the future. As a part of Stratospheric-tropospheric Processes and their Role in Climate (S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…Carbonyl sulfide (OCS) makes the second largest contribution to the aerosol layer. These sulfur species originate at the Earth's surface in a variety of reduced forms (including CS 2 , DMS and H 2 S) before oxidation in the atmosphere (Kremser et al, 2016). Other sources of stratospheric aerosol include the transport of tropospheric aerosol across the tropical tropopause through large convective systems such as the Asian monsoon (Vernier et al, 2011a;Thomason and Vernier, 2013).…”
Section: The Importance Of Stratospheric Aerosol Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Carbonyl sulfide (OCS) makes the second largest contribution to the aerosol layer. These sulfur species originate at the Earth's surface in a variety of reduced forms (including CS 2 , DMS and H 2 S) before oxidation in the atmosphere (Kremser et al, 2016). Other sources of stratospheric aerosol include the transport of tropospheric aerosol across the tropical tropopause through large convective systems such as the Asian monsoon (Vernier et al, 2011a;Thomason and Vernier, 2013).…”
Section: The Importance Of Stratospheric Aerosol Measurementsmentioning
confidence: 99%
“…Over the past few years, there has been a rising interest in the geoengineering concept for solar radiation management, by injecting aerosol into the stratosphere (Rasch et al, 2008), for which a basic understanding of the present stratospheric aerosol layer is essential. A review paper by Kremser et al (2016) concluded that it is critical to maintain continuous observational records to detect unpredictable events (like large volcanic eruptions) or unexpected developments (such as non-volcanic processes like strong PyroCb events that result in changes in stratospheric aerosol levels), noting that observations are critical for testing the reliability of climate models.…”
Section: The Importance Of Stratospheric Aerosol Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, as sulfuric acid aerosol particles absorb upwelling infrared radiation, the presence of a volcanic aerosol layer can change the thermal structure of the stratosphere (Labitzke, 1994) and the troposphere and modulate stratospheric circulation as well as transport across the tropopause (Pitari et al, 2016). Significant effort has been expended toward measuring stratospheric aerosol using a variety of instruments (Kremser et al, 2016), and an extensive data collection of observations are now available. Some global climate models (GCMs) and Earth system models (ESMs) use these measurements or parameters directly derived from them (Mann et al, 2015), whereas others, which L. W. Thomason et al: Evidence for the predictability of changes in the stratospheric aerosol size use interactive aerosol model schemes (Mills et al, 2016) and similar tools (Toohey et al, 2016), assess how well their tools replicate observations and, thus, infer the reliability of the models' assessment of the climate impact of volcanic eruptions (Timmreck et al, 2016).…”
Section: Introductionmentioning
confidence: 99%